Sol-gel Synthesis of Silicadioxide/Organopolymer Nanocomposite for Potential Applications in EOR Nanotechnology - Soleimani, H. (Springer Science and Business Media Deutschland GmbH, 2022)
The application of enhanced oil recovery (EOR) nanotechnology has opened an important field of fundamental science and engineering studies offering a wide range of research interests. Owing to the physicochemical properties of some nanoparticles (NPs), several mechanisms have been employed to functionalize the surface of nanoparticles to improve the interface between organic and inorganic molecules. In this study, a Î²-1,3-glucan schizophyllan organopolymer (SPG-OH) was grafted onto hydroxyl activated silica NPs (SiO2âOH NPs) via a sol-gel thermo-condensation polymerization process to further improve the surface properties of the SiO2 NPs. The structure of the nanocomposite material (SPG-g-SiO2 NPs) was characterized using different spectroscopic experiments such as FTIR, FESEM, XRD and TGA. From the spectroscopic experiments, the grafting bonding between the SPG-OH and the SiO2âOH NPs was established in the FTIR spectra of the SPG-g-SiO2 NPs due to the disappearance of the characteristic absorption wavelength corresponding to âOH at 3303â3500 cmâ1 leading to strong chemical interactions between the SPG and SiO2 NPs. Although, there was noticeable slight modification of the size and environment of the SPG-g-SiO2 NPs composite due to surface activity in the FESEM imaging, however, a large proportion of these grafted particles were within 20â30 nm indicating minimum particle aggregations. The XRD experiments further confirmed that no surface morphology change from amorphous to crystalline was observed due to the appearance of diffraction shoulder at 20 2Î¸ in the diffractogram. Similarly, the grafted material had a 53 residual mass after subjected to 800Â â decomposition temperature, indicating thermal stability. Thus, this study suggests that a composite of the SPG-g-SiO2 NPs could potentially be utilized in the EOR nanotechnology, such as in smart nanofluid injection or combined with surfactant in foam flooding for enhancing oil recovery. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.